2000
DOI: 10.1016/s0168-8278(00)80425-0
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH) is a rare disease, characterized by female predominance, hypergammaglobulinemia, autoantibodies, association with HLA DR3 and HLA DR4 and a good response to immunosuppression. Different subtypes of AIH may be distinguished, based on differences in the autoantibody patterns. AIH type 1 is characterized by anti-nuclear (ANA) and/or anti-smooth muscular (SMA) autoantibodies. AIH type 2 is characterized by liver/kidney microsomal autoantibodies (LKM). AIH type 3 may be distinguished by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
13

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 125 publications
2
89
0
13
Order By: Relevance
“…39 Several drugs or chemicals have been shown to induce hepatitis with autoimmune involvement, e.g., tienilic acid, dihydralazine, and halothane. 40 The most intimately associated xenobiotic-induced liver disease associated with PBC, halothane hepatitis, occurs when susceptible patients mount an immune response to trifluoroacetylated protein antigens, formed following cytochrome P450 -mediated bioactivation of halothane to trifluoroacetyl chloride. 41 Exposure to trifluoroacetyl acid (TFA)-conjugated self proteins, both in humans and experimental animals, has led to antibody responses against such TFA-self proteins.…”
Section: Chemical Xenobiotic and Diseasementioning
confidence: 99%
“…39 Several drugs or chemicals have been shown to induce hepatitis with autoimmune involvement, e.g., tienilic acid, dihydralazine, and halothane. 40 The most intimately associated xenobiotic-induced liver disease associated with PBC, halothane hepatitis, occurs when susceptible patients mount an immune response to trifluoroacetylated protein antigens, formed following cytochrome P450 -mediated bioactivation of halothane to trifluoroacetyl chloride. 41 Exposure to trifluoroacetyl acid (TFA)-conjugated self proteins, both in humans and experimental animals, has led to antibody responses against such TFA-self proteins.…”
Section: Chemical Xenobiotic and Diseasementioning
confidence: 99%
“…[1][2][3] Studies of LSP revealed that antibody to the asialoglycoprotein receptor was a specific marker of AIH. 4,5 In addition, recent evidence indicates that there may be several autoantibodies that recognize hepatocyte-associated molecules.…”
mentioning
confidence: 99%
“…This was also our patient's phenotype. In Czaja's study a high proportion of patients were HLA-DR17, which is associated with poorer outcome (23)(24)(25). (27).…”
Section: Discussionmentioning
confidence: 99%